Thermal mortars : contribution of the incorporation of PCM microcapsules - Cunha, Sandra Raquel Leite (2012)
The main purpose of this work is the production of a mortar with incorporation of Phase Change Materials (PCM) microcapsules, which must have a compromise between workability, mechanical strength and aesthetic appearance. The mortars studied in this work are mixed mortars of lime and gypsum. The proportion of PCM is 0%, 10%, 20% and 30%. In order to minimize some problems associated with shrinkage and consequent cracking of the mortars, the incorporation of nylon fibers, superplasticizer and gypsum was tested. A studied of mechanical characteristics and some sensitivity tests for qualify the shrinkage of the fifteen compositions was realized. In this way, one composition for the application in tests cells was selected, with the aim of studying the thermal behaviour of these mortars. The test performed on test cells includes the study of a standard mortar without addition of PCM and a mortar with incorporation of an ideal percentage of PCM. Based on the obtained results it was possible to conclude that the incorporation of PCM microcapsules in the studied mortars causes an increase in mechanical strengths and shrinkage. The tests performed on test cells allowed to verify a time lag in maximum and minimum temperatures, as well as a slight attenuation in the temperature variation. It can be concluded that the use of PCM microcapsules in mixed mortars of lime and gypsum can be assumed as a viable solution for applications in the construction industry once these present a compromise between their resistance, aesthetic appearance and thermal behaviour.